Impacto del transporte de la codorniz japonesa a cuatro edades desde la costa a la sierra peruana en el inicio de la puesta y el rendimiento productivo - Paredes, Manuel (2024)
The impact of transporting quail of four ages (0, 14, 28 and 42 days) from the coast to the Peruvian mountains on the onset of oviposition and performance in the laying phase was measured. The quails were moved from Lurin (Lima, Peru) at 14 meters above sea level to the Cajamarca valley at 2743 meters above sea level. A batch of 800 recently hatched female chicks in Lurin to distribute them in four groups of 200 birds each. Three groups were installed in Lurin and one group was taken to Cajamarca on the same day of birth. The other groups were transferred at 14, 28 and 42 days of age to Cajamarca. At 42 days of age, the birds were distributed per treatment at a rate of 15 birds per cage (one cage = one repetition). Each treatment had six repetitions. Quails transferred at 14, 28 and 42 days of age reached higher body weights and egg weights at the beginning of laying, with greater egg mass and better laying rate during the productive phase. Quails transferred at 28 and 42 days of age began laying at a younger age and with better feed conversion at laying.